The Effect of Cysteine on the Removal of Cadmium in Paddy Soil by Combination with Bioremediation and the Response of the Soil Microbial Community - Emmanuel Konadu Sarkodie; Kewei Li; Ziwen Guo; Jiejie Yang; Yan Deng; Jiaxin Shi; Yulong Peng; Yuli Jiang; Huidan Jiang; Hongwei Liu; Yili Liang; Huaqun Yin; et al. (Toxics)
Bioremediation is widely recognized as a promising and efficient approach for the elimination of Cd from contaminated paddy soils. However, the Cd removal efficacy achieved through this method remains unsatisfactory and is accompanied by a marginally higher cost. Cysteine has the potential to improve the bioleaching efficiency of Cd from soils and decrease the use cost since it is green, acidic and has a high Cd affinity. In this study, different combination modes of cysteine and microbial inoculant were designed to analyze their effects on Cd removal and the soil microbial community through the sequence extraction of Cd fraction and high-throughput sequencing. The results demonstrate that the mixture of cysteine and the microbial inoculant was the best mode for increasing the Cd removal efficiency. And a ratio of cysteine to microbial inoculant of 5 mg:2 mL in a 300 mL volume was the most economically efficient matching. The Cd removal rate increased by 7.7–15.1% in comparison with the microbial inoculant treatment. This could be ascribed to the enhanced removal rate of the exchangeable and carbonate-bound Cd, which achieved 94.6% and 96.1%, respectively. After the treatment, the contents of ammonium nitrogen (NH3–N), total phosphorus (TP), available potassium (AK), and available phosphorus (AP) in the paddy soils were increased. The treatment of combinations of cysteine and microbial inoculant had an impact on the soil microbial diversity. The relative abundances of Alicyclobacillus, Metallibacterium, and Bacillus were increased in the paddy soils. The microbial metabolic functions, such as replication and repair and amino acid metabolism, were also increased after treatment, which benefitted the microbial survival and adaptation to the environment. The removal of Cd was attributed to the solubilizing, complexing, and ion-exchanging effects of the cysteine, the intra- and extracellular adsorption, and the production of organic acids of functional microorganisms. Moreover, cysteine, as a carbon, nitrogen, and sulfur source, promoted the growth and metabolism of microorganisms to achieve the effect of the synergistic promotion of microbial Cd removal. Therefore, this study underscored the potential of cysteine to enhance the bioremediation performance in Cd-contaminated paddy soils, offering valuable theoretical and technical insights for this field.